FINANCIAL PROVISION OF RUSSIAN ECONOMY MODERNIZATION - Igor A. Yeremenko; Elena N. Rudskaya (Advanced Engineering Research, 2012)
The use of budget funds, direct investment funds, and venture capital funds as the major sources of the modernization financial assets is analyzed. General financial instruments for stimulating the Russian economy modernization are specified.